Hydrology of Artificial and Controlled Experiments - Liu, Jiu-Fu; Gu, Wei-Zu (IntechOpen, 2018)
For the incisive tests of hydrological theory, manipulation experiments can create particular conditions, plan and define boundaries and inner structures, isolate individual mechanisms, and push systems beyond the range in a PhD timescale. The goals of this book are to stimulate the approach of manipulation in promoting watershed hydrological experimentation and to try to demonstrate that the controlled and artificial experiments are the promising way of useful and effective generation of tests of new theories. This book is organized on the basis of nine different manipulation types from six countries including field lysimeter, field runoff plot, field manipulated experimental basin, field artificial catchment, laboratory river segment, laboratory pedon (rock), laboratory lysimeter, laboratory hillslope, and phytotron artificial catchment.